2016
DOI: 10.1016/j.ebiom.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cognitive Function in Older Adults Using a Videoconference Approach

Abstract: BackgroundThe use of communication technologies is an emerging trend in healthcare and research. Despite efficient, reliable and accurate neuropsychological batteries to evaluate cognitive performance in-person, more diverse and less expensive and time consuming solutions are needed. Here we conducted a pilot study to determine the applicability of a videoconference (VC, Skype®) approach to assess cognitive function in older adults, using The Telephone Interview for Cognitive Status-Modified – Portuguese versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
(36 reference statements)
2
30
3
Order By: Relevance
“…Technological feasibility mostly related to the audio‐visual quality of the TM session. Audio‐visual quality was deemed “inadequate” 22% of the time in one study (Shores et al, ) and “poor” among 11.5% of participants in another study (Castanho et al, ). In the study of Schulz et al (), which used video‐interpreting, audio echo and picture quality affected TM sessions in 15% of patients and 22% of clinicians (Schulz et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological feasibility mostly related to the audio‐visual quality of the TM session. Audio‐visual quality was deemed “inadequate” 22% of the time in one study (Shores et al, ) and “poor” among 11.5% of participants in another study (Castanho et al, ). In the study of Schulz et al (), which used video‐interpreting, audio echo and picture quality affected TM sessions in 15% of patients and 22% of clinicians (Schulz et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Agreement is a measure of how similar results are between repeated measures, while reliability is defined as how well individual patients are distinguishable from each despite measurement errors (de Vet, Terwee, Knol, & Bouter, ). Eleven papers were found that measured agreement and reliability of neurocognitive assessments administered by TM compared with either FTF or telephone methods (Castanho et al, ; Cullum et al, ; Cullum et al, ; Galusha‐Glasscock et al, ; Grosch et al, ; Loh et al, ; Loh, Donaldson, Flicker, Maher, & Goldswain, ; Martin‐Khan et al, ; McEachern, Kirk, Morgan, Crossley, & Henry, ; Wadsworth et al, ; Wong, Martin‐Khan, Rowland, Varghese, & Gray, ). The most common neurocognitive assessments administered in these studies include MMSE (Castanho et al, ; Cullum et al, ; Cullum et al, ; Galusha‐Glasscock et al, ; Grosch et al, ; Loh et al, ; Loh et al, ; Martin‐Khan et al, ; McEachern et al, ; Wadsworth et al, ), Geriatric Depression Scale (GDS) (Loh et al, ; Loh et al, ), and RUDAS (Martin‐Khan et al, ; Wong et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…exploring issues of usability and acceptability). 45,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Many focus specifically on the clinical use of Skype, 91,[114][115][116][117][118][119][120][121][122][123] either on its own or in combination with other technologies [e.g. WhatsApp (WhatsApp Inc., Mountain View, CA, USA) messaging 124 or FaceTime 125,126 ].…”
Section: Evidence Relating To the Use Of Virtual Consultationsmentioning
confidence: 99%
“…One study showed a moderate difference between FTF and telehealth scores . The Portuguese study showed as well high correlations and strong associations between the 3 approaches (VC, FTF, and telephone‐based testing). The studies using a single approach (VC/VTC assessments) show that patients, caregivers as well as physicians report high satisfaction with this application.…”
Section: Discussionmentioning
confidence: 94%
“…Most of the studies included in this category (see Table ) originate from the USA ( n = 10) . Four included studies are from Australia, 3 from Canada, and one study has been conducted in Portugal …”
Section: Resultsmentioning
confidence: 99%